Contas econômicas ambientais da energia no Brasil e a energia solar fotovoltaica - Mário Rubens Figueiredo Barroso (2019)
With the regulation of the energy sector since 2012 and the establishment of the energy compensation system in the country, there has been an expansion of the photovoltaic market. This expansion is due to the greater legal certainty provided to investors in the energy sector in Brazil, as well as to the increase in the financial viability of photovoltaic generation projects, due to factors such as: the reduction of the cost of components of photovoltaic generation systems, the cost of electric power supplied by the concessionaires, the increase in the supply of specialized labor and the competitiveness among integrating companies. The present work aims to present the energy matrix used in the various sectors of the Brazilian economy, adopting the method of Economic Environmental Accounting - Energy, from the English "System of Economic Energy Accounting" (SEEA-Energy) adopted by the United Nations UN). The methodology used was to fill in the Available and Used Energy Physical Resources Sheets (PSUT) and, later, to fill out the Available and Used Money Resource Sheet (MSUT), using data from the Brazilian energy matrix. The analysis of the results showed: (i) the percentage of use of each energy source in the different Brazilian productive sectors; and (ii) the cost of energy products for each sector of the Brazilian economy. It was concluded that (i) electric energy is the highest value-added energy product in the Brazilian energy matrix; (ii) the highest cost of electric energy falls on the consumer of the residential sector; (iii) the generation of photovoltaic solar energy, in the decentralized mode, is a possibility of reducing costs for consumers in the residential and commercial sector and should be encouraged.